2011
DOI: 10.1149/1.3615988
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wafer Geometry on CMP for Advanced Nodes

Abstract: Material removal uniformity during chemical mechanical polishing (CMP) for IC fabrication processes such as shallow trench isolation has previously been shown to be affected by nanotopography (NT) of the wafer frontside (pattern surface). NT is the high frequency height variations of the wafer surface within spatial wavelengths from 0.2 to 20 mm. However, the effect of other topography information such as wafer backside NT and the relatively lower frequency wafer shape on CMP have not been addressed sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Otherwise, it has been shown that the across-wafer CMP material removal uniformity also depends on wafer geometry features such as wafer shape, nanotopography which is different from the design pattern topography. [32][33][34] However, the model could not include all the factors which affect the contact pressure. Therefore, the complicated contact problem is ECS Journal of Solid State Science and Technology, 3 (4) P60-P74 (2014) P63 simplified in order to quantify the contact pressure distribution on the feature scale.…”
Section: Modelingmentioning
confidence: 99%
“…Otherwise, it has been shown that the across-wafer CMP material removal uniformity also depends on wafer geometry features such as wafer shape, nanotopography which is different from the design pattern topography. [32][33][34] However, the model could not include all the factors which affect the contact pressure. Therefore, the complicated contact problem is ECS Journal of Solid State Science and Technology, 3 (4) P60-P74 (2014) P63 simplified in order to quantify the contact pressure distribution on the feature scale.…”
Section: Modelingmentioning
confidence: 99%
“…Detailed definitions of the wafer geometry of Si wafers are specified by an SEMI standard. 5 Wafer geometry can be classified into components 6 that span different ranges of spatial wavelengths (λ). For example, roughness of a wafer is defined by very high frequency variations with λ < 0.2 mm, followed by nanotopography (NT) variations with λ ranging from a few tenths of a mm to 20 mm.…”
Section: Relationship Between Wafer Geometry Andmentioning
confidence: 99%
“…Since the introduction of nanotopography metrics, the surface topography of incoming wafers has improved tremendously, which has driven a significant enhancement of CMP and lithography performance. [10][11][12][13][14][15][16] z E-mail: jaydeep.sinha@kla-tencor.com; joann.q.qiu@intel.com Historically, the edge dies on a wafer always yield lower compared to the center dies. To maximize the edge die yield, the wafer edge geometry characteristics need to be well understood.…”
mentioning
confidence: 99%